Pengaruh Pengumuman Unusual Marker Activity Terhadap Abnormal Return dan Trading Volume Activity - Tarigan, Agnes Monika; Trimeiningrum, Eny (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
This study aims to analyze the response of the Indonesian capital market to the announcement of Unusual Market Activity (UMA) issued by the Indonesia Stock Exchange (IDX) by examining abnormal return and trading volume activity (TVA) of listed stocks during the 2023–2024 period. The research employs a quantitative approach using an event study methodology, with an observation window of 11 days consisting of five days before the announcement, one day on the announcement date, and five days after the UMA announcement. The research sample was determined using purposive sampling, resulting in 168 UMA announcement events that met the research criteria. Data were analyzed using normality tests, followed by the Wilcoxon Signed Rank Test due to non-normal data distribution. The findings reveal a significant difference in abnormal return before and after the UMA announcement in both 2023 and 2024, indicating that UMA announcements contain information that is responded to by the market through stock price adjustments. However, the analysis of trading volume activity shows no significant difference before and after the UMA announcement in both periods. These results provide empirical evidence that UMA announcements exert an asymmetric impact on market reactions and support the notion that the Indonesian capital market exhibits characteristics consistent with semi-strong form market efficiency